Employing recent technologies for improved digital governance - Ponnusamy, Vasaki 1974-; Rafique, Khalid 1973-; Zaman, Noor 1972- (IGI Global, 2019)
"This book explores recent advances in the development, application, and impact of technologies in digital governance"--
Description based on title screen (IGI Global, viewed 12/28/2019)
Keywords: Public administration / Data processing; Municipal services / Data processing; Internet in public administration